2007
DOI: 10.1017/s0007114507252675
|View full text |Cite
|
Sign up to set email alerts
|

Growth and body composition in children with chronic kidney disease

Abstract: Growth failure is a common yet complex problem of childhood chronic kidney disease caused by multiple factors encountered due to the primary disease or secondary to the renal impairment. This review seeks to describe the various patho-physiological mechanisms contributing to growth failure in the various stages of childhood with particular emphasis on nutritional problems and endocrine dysfunction encountered whilst managing these children. In addition, we shall examine the role of body composition in chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 90 publications
0
7
1
Order By: Relevance
“…Unlike some studies, which reported elevated adiposity in CKD, 33 we observed significantly elevated whole body FM Zscores only among CKD 4 to 5 participants. However, our findings regarding fat distribution were consistent with prior reports, indicating central distribution of adiposity in both children 12 and adults 20 with CKD.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike some studies, which reported elevated adiposity in CKD, 33 we observed significantly elevated whole body FM Zscores only among CKD 4 to 5 participants. However, our findings regarding fat distribution were consistent with prior reports, indicating central distribution of adiposity in both children 12 and adults 20 with CKD.…”
Section: Discussioncontrasting
confidence: 99%
“…Previously, we showed that AgRP attenuated cachexia in CKD mice (8,10). Although promising, our previous studies (38,39) with AgRP have one major caveat, as we used dual energy X-ray absorptiometry (DXA) to assess the body composition in mice. DXA cannot measure body water.…”
mentioning
confidence: 99%
“…Causes of growth failure include in CKD disturbances in growth hormone (GH) metabolism and insulin-like growth factor-I (IGF-I), electrolyte abnormalities, nutritional deficiency, metabolic acidosis, uremia, anemia, and inflammation ( 2 , 16 , 17 , 21 23 ). Other hormonal changes in CKD that adversely affect growth include vitamin D deficiency, hyperparathyroidism, and hypogonadism ( 24 26 ).…”
Section: Causes Of Growth Impairment In Ckdmentioning
confidence: 99%
“…The prevalence of ESRD is about nine per one million children in the United States, with the highest incidence of new patients with ESRD appearing in early and mid-adolescence ( 1 ). Despite advances in the diagnosis and care of children with CKD, many will progress to ESRD ( 2 ). Growth failure is a major complication of CKD.…”
Section: Introductionmentioning
confidence: 99%